Fenomena Hukum Pengajuan Kepailitan Terhadap Pengusaha Oleh Pekerja Karena Hak Pekerja Yang Tidak Dibayar Pengusaha - Shubhan, M. Hadi (UI Scholars Hub, 2023)
This study examined industrial relations in Indonesia regarding workers’ tendency to use bankruptcy legal instruments by filing bankruptcy against the related company over their unpaid rights (wages and severance). In the normal course of completion, workers will take legal action through industrial relations dispute settlement, which is characterized by pure civil law in defending their unpaid rights. However, legal remedies through industrial relations dispute settlements are often ineffective due to various causes and backgrounds. This study found that there was an alternative use of legal remedies by workers in fighting for their unpaid rights by filing bankruptcy against the related company, which was more effective than taking legal measures to resolve industrial relations disputes. The legal remedies in the form of bankruptcy used by workers to achieve their unpaid rights are possible in bankruptcy law and labor law in Indonesia.